Answer:
im sry could u pls rewrite the expression?
Step-by-step explanation:
Answer:
- (0, 4)
- (-1, 16/ 3)
- (-9/ 2, 10)
Step-by-step explanation:
In an ordered pair the term before the comma is the x variable and the term after the comma is the y variable.
1.
4x + 3y = 12 . . . . . .(0, _)
here were given the x variable
finding the other term
4× 0 + 3y = 12
3y = 12
y = 4
therefore the ordered pair is <u>(0, 4) </u>
2.
. . . . . . . (-1, _)
here were given the x variable
4 × -1 + 3y = 12
3y = 12 + 4
3y = 16
y = 16/ 3
ordered pair is <u>(-1, 16/ 3)</u>
3.
. . . . . . . . (_, 10)
here were given the y variable
finding the other term
4x + 3 × 10 = 12
4x + 30 = 12
4x = 12 - 30
4x = -18
dividing both sides by 2
2x = -9
x = -9/ 2
ordered pair is<u> (-9/ 2, 10)</u>
Answer:
Option D is correct.
13x = 39
Step-by-step explanation:
The system of equation is given:
....[1]
.....[2]
Multiply equation [1] by 5 to both sides we have;
.....[3]
Using elimination method:
Add [2] and [3] equations to eliminate y and solve for x, we have;
![13x = 39](https://tex.z-dn.net/?f=13x%20%3D%2039)
Divide both sides by 13 we get;
x = 3
Substitute x in [1] we have;
2(3)-y = -4
6-y = -4
Subtract 6 from both sides we have;
-y = -10
Divide both sides by -1 we have;
y = 10
⇒Solution: (3, 10)
Therefore, an equation can replace 3x+5y = 59 in the original system and still produce the same solution is,
13x = 39
Answer:
undefined
Step-by-step explanation:
f(x) = 2/ (-5x-10)
Let x = -2
f(-2) = 2/ (-5(-2)-10)
=2/(10-10)
=2/0
= undefined